Energetska samozadostnost planinskih postojank v Triglavskem narodnem parku - Jensterle, Urban (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
The electricity supply of mountain huts in Triglav National Park has changed in last 20 years. It is no longer based on fossil fuels but on renewable energy sources. In summer 2012, all analyzed mountain huts had solar cells, some also used wind energy. We are pre - senting a typology of mountain huts according to energy supply, their needs for energy, electricity and heat supply. Proposals and priorities were set for those mountain huts who still use fossil fuels for electricity production.
Keywords: Julian Alps; Julijske Alpe; obnovljivi energetski viri; planinske koče; preskrba z energijo; Slovenia; Slovenija; sončna energija; Triglav National Park; Triglavski narodni park